Effects of Single Pill Combinations Compared to Identical Multi Pill Therapy on Outcomes in Hypertension, Dyslipidemia and Secondary Cardiovascular Prevention: The START-Study - Wilke T; Weisser B; Predel HG; Schmieder R; Wassmann S; Gillessen A; Blettenberg J; Maywald U; Randerath O; Mueller S; Böhm M (Dove Medical Press, 2022)
Thomas Wilke,1 Burkhard Weisser,2 Hans-Georg Predel,3 Roland Schmieder,4 Sven Wassmann,5 Anton Gillessen,6 Jörg Blettenberg,7 Ulf Maywald,8 Olaf Randerath,9 Sabrina Mueller,10 Michael Böhm11 1Institut für Pharmakoökonomie und Arzneimittellogistik (IPAM)/Institute for Pharmacoeconomics and Pharmaceutical Logistics, Wismar, Germany; 2Institute of Sports Science, Christian-Albrechts-University of Kiel, Kiel, Germany; 3Institute of Cardiology and Sports Medicine, German Sport University, Cologne, Germany; 4Department of Nephrology and Hypertension, University Hospital Erlangen, Friedrich Alexander University Erlangen Nürnberg, Erlangen, Germany; 5Faculty of Medicine, Cardiology Pasing, Munich and University of the Saarland, Homburg/Saar, Germany; 6Department of Internal Medicine, Herz-Jesu-Hospital, Münster, Germany; 7Practice Dr. J. Blettenberg, Lindlar, Germany; 8AOK PLUS - The Health Insurance for Sachsen und Thüringen; GB Medicines/Remedies, Dresden, Germany; 9Medical Department, APONTIS PHARMA GmbH & Co.KG, Monheim, Germany; 10Ingress-Health HWM GmbH, Wismar, Germany; 11Clinic for Internal Medicine III, University Clinic of Saarland, Saarland University, Homburg/Saar, GermanyCorrespondence: Thomas Wilke, Institute of Pharmacoeconomics and Medication Logistics, University of Wismar, Alter Holzhafen 19, Wismar, 23966, Germany, Tel +4938417581014, Fax +4938417581011, Email Thomas.wilke@ipam-wismar.deAim: Current guidelines for the treatment of arterial hypertension (AH) or cardiovascular (CV) prevention recommend combination drug treatments with single pill combinations (SPC) to improve adherence to treatment. We aimed to assess whether the SPC concept is clinically superior to multi pill combination (MPC) with identical drugs.Methods and Results: In an explorative study, we analyzed anonymized claims data sets of patients treated with CV drugs for hypertension and/or CV disorders who were insured by the German AOK PLUS statutory health fund covering 01/07/2012-30/06/2018. Patients at age ≥ 18 years who received either a SPC or MPC with identical drugs were followed for up to one year. A one to one propensity score matching (PSM) was applied within patient groups who started identical drug combinations, and results were reported as incidence rate ratios (IRRs) as well as hazard ratios (HRs). After PSM, data from 59,336 patients were analyzed. In 30 out of 56 IRR analyses, superiority of SPC over MPC was shown. In 5 out of 7 comparisons, the HR for the composite outcome of all-cause death and all-cause hospitalizations was in favor of the SPC regimen (SPC versus MPC): valsartan/amlodipine: HR=0.87 (95% CI: 0.84- 0.91, p ≤ 0.001); candesartan/amlodipine: 0.77 (95% CI: 0.65- 0.90, p = 0.001); valsartan/amlodipine/hydrochlorothiazide: HR=0.68 (95% CI: 0.61- 0.74, p ≤ 0.001); ramipril/amlodipine: HR=0.80 (95% CI: 0.77- 0.83, p ≤ 0.001); acetylsalicylic acid (ASA)/atorvastatin/ramipril: HR=0.64 (95% CI: 0.47- 0.88, p = 0.005).Conclusion: SPC regimens are associated with a lower incidence of CV events and lower all-cause mortality in clinical practice. SPC regimens should generally be preferred to improve patient's prognosis.Keywords: single pill, adherence, cardiovascular outcomes, mortality, prognosis, clinical practice